BISINDO-based instructional videos in inclusive vocational welding learning: Preliminary evidence from a single-subject study - Rochmad Novian Inderanata; Setuju Setuju; Dinar Westri Andini; Putu Sudira; Sutopo Sutopo; Septian Rahman Hakim; Esta Larossa; Paterson Nji Mbakwa (Jurnal Pendidikan Vokasi, 2026)
This study examined within-participant changes in procedural understanding, practical welding skills, and learning engagement following the introduction of Indonesian Sign Language (BISINDO)-based instructional videos for a vocational high school student with hearing impairment. The study employed an A–B single-subject design comprising three baseline sessions and three intervention sessions. Outcomes were assessed using structured observation rubrics and converted to scores on a 0–100 scale. The participant was one student with hearing impairment enrolled in a basic welding course at a vocational high school. Data were collected through repeated observations across six learning sessions, consisting of three baseline sessions and three intervention sessions. The instruments included observation sheets assessing procedural understanding, practical welding skills, learning engagement, and intervention implementation. Data were analyzed using visual analysis across conditions and the Percentage of Non-overlapping Data (PND) to identify changes between the baseline and intervention phases. The results indicated positive within-participant changes across all observed variables following the introduction of BISINDO-based instructional videos. All intervention observations exceeded the highest baseline observations, resulting in a PND value of 100% for each outcome. However, these findings should be interpreted with caution due to the short duration of each phase and the absence of experimental replication. For the participant in this study, the introduction of BISINDO-based instructional videos was associated with higher observed scores in procedural understanding, practical welding skills, and learning engagement. Further research employing more rigorous single-case designs and involving additional participants is needed before broader conclusions can be drawn.